The presence of the ICT in the subjects of music of the Teacher's Degrees: an analysis of the educational plans - Calderon-Garrido, Diego; Carrera, Xavier; Gustems-Carnicer, Josep (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2021)
The educational university plans represent a commitment between the institution and the students, by means of which the what, when, how, why and for what the different contents of a subject will be developed. This study analyzes the presence of ICT in all educational plans of the subjects referred to the Music Education of the Degrees of Teacher of Childhood Education, Teacher of Primary Education and Double Degree (in its different modalities) of all Spanish universities (N = 892) and the differences are looked for according to the grades, the pertinence to the mention of music and the modality of delivery of each subject. The analysis of their competences, content blocks, activities, evaluation and documentary sources allows to affirm that ICTs are not present in these plans, so the training of future teachers in the current context should be reinforced in this sense.
Keywords: Teaching plans; Music Education; childhood education; primary education; double degree education; ICT